2001
DOI: 10.1002/mrm.1282.abs
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution intracranial and cervical MRA at 3.0T: Technical considerations and initial experience

Abstract: Initial experience with intracranial and cervical MRA at 3.0T is reported. Phantom measurements (corrected for relaxation effects) show S/N (3.0T) ‫؍‬ 2.14 ؎ 0.08 ؋ S/N (1.5T) in identical-geometry head coils. A 3.0T 3DTOF intracranial imaging protocol with higher-order autoshimming was developed and compared to 1.5T 3DTOF in 12 patients with aneurysms. A comparison by two radiologists showed the 3.0T to be significantly better (P < 0.001) for visualization of the aneurysms. The feasibility of cervical and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0
3

Year Published

2002
2002
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 5 publications
3
48
0
3
Order By: Relevance
“…Expectedly, also inflow angiographies profit from the higher magnetic field [21,22,23]. Image quality in terms of resolution of small vessels was still inferior to DSA (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Expectedly, also inflow angiographies profit from the higher magnetic field [21,22,23]. Image quality in terms of resolution of small vessels was still inferior to DSA (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…As the signal scales proportionally with the field strength, 3.0T holds potential benefits for cardiovascular MR imaging [6][7][8][9][10][11][12][13][14][15]. The feasibility of higher spatial resolution in MRA of the intracranial and carotid arteries at 3.0T has been the subject of various studies [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the performance of 3D-TOF MRA at 3 T is significantly better than at 1.5 T [38]. However the problems associated with 3D-TOF discussed above remain significant at 3 T also.…”
Section: Discussionmentioning
confidence: 89%
“…In addition timing problems exist with this technique in order to eliminate venous contamination in the setting of slow flow. In addition, the use of CE-MRA at 3 T introduces specific RF power deposition concerns that need to be addressed [38] through the careful selection of TR and flip angle values.…”
Section: Discussionmentioning
confidence: 99%